Evolution of multiple quantum coherences with scaled dipolar Hamiltonian - Sánchez, Claudia Marina; Buljubasich Gentiletti, Lisandro; Pastawski, Horacio Miguel; Chattah, Ana Karina (2024)
Artículo finalmente publicado en: Sánchez, C. M., Buljubasich, L., Pastawski, H. M. y Chattah, A. K. (2017). Evolution of multiple quantum coherences with scaled dipolar Hamiltonian. Journal of Magnetic Resonance, 281, 75-81. http://dx.doi.org/10.1016/j.jmr.2017.05.009